SISTEM INFORMASI PERHIMPUNAN MAHASISWA KATOLIK REPUBLIK INDONESIA SANTU FRANSISKUS XAVERIUS CABANG KUPANG BERBASIS MOBILE WEB - Benyamin Jago Belalawe Beny (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
Indonesian Catholic Student Association (PMKRI) St. Fransiskus Xaverius Kupang Branch was established on October 25, 1963, which is one of the student organizations with national standards. This organization includes students who are pursuing higher education in Kupang City from 21 regencies in East Nusa Tenggara Province. A mobile web-based information system is one of the requirements for a national organization that ensures the security and speed of data access. In this case, especially the Kupang branch of PMKRI which has not utilized technology.